TT-SET augmented with POT: a potential framework for academics' pedagogical reasoning. Issue 1 (2nd January 2020) - Nguyen, Phuong Vu
ABSTRACT: This paper discusses academics' perceptions of the use of teacher-tailored student evaluation of teaching (TT-SET) augmented with peer observation of teaching (POT) for promoting their reflection in the process of pedagogical reasoning. This constructivist qualitative case study involved 11 academics teaching English at a university in Vietnam. Data were collected through multiple data collection methods and analysed inductively and thematically. The findings suggested that the theoretical framework developed for this study helped explain the changes in academics' pedagogical reasoning, particularly reflection, leading to academics' new comprehension of practice, attempted changes to improve practice, enhanced self-efficacy, and improved collaboration and collegiality. Several challenges found during the implementation of the intervention suggested that contextual and cultural factors need considering in a revised framework for it to be successful.